A psychiatric perspective view of bariatric surgery patients (Archives of Clinical Psychiatry, 2015)
Background Bariatric surgery is the only procedure that has significant results in weight loss and improvements in medical comorbidities in morbid obese patients. Severely obese patients are also associated with a higher prevalence of psychiatric disorders and poor quality of life. Objective To evaluate specific areas of psychopathology in individuals undergoing bariatric surgery. Methods A review of the literature was conducted from January 2002 to March 2014 by researching PubMed database using the following query: “morbid AND obesity AND bariatric AND surgery AND (psychiatry OR psychology)”. Results Overall improvements in eating behaviors, mood disorders and body image are reported after bariatric surgery, and the mechanism is not enlightened. Risk of suicide and consumption of substances of abuse, especially alcohol, after gastric bypass surgery are problems that clinicians must be aware. Discussion Bariatric patients should be monitored after surgery to identify who did not show the expected benefits postoperatively and the ones who develop psychiatric symptoms after an initial positive response.